A new writing classroom : listening, motivation, and habits of mind - Sullivan, Patrick, 1956- (Utah State University Press, 2014)
In A new writing classroom, Patrick Sullivan provides a new generation of teachers a means and a rationale to reconceive their approach to teaching writing, calling into question the discipline's dependence on argument. Including secondary writing teachers within his purview, Sullivan advocates a more diverse, exploratory, and flexible approach to writing activities in grades six through thirteen. A new writing classroom encourages teachers to pay more attention to research in learning theory, transfer of learning, international models for nurturing excellence in the classroom, and recent work in listening to teach students the sort of dialogic stance that leads to higher-order thinking and more sophisticated communication. The conventional argumentative essay is often a simplistic form of argument, widely believed to be the most appropriate type of writing in English classes, but other kinds of writing may be more valuable to students and offer more important kinds of cognitive challenges. Focusing on listening and dispositions or "habits of mind" as central elements of this new composition pedagogy, A new writing classroom draws not just on composition studies but also on cognitive psychology, philosophy, learning theory, literature, and history, making an exciting and significant contribution to the field